Role of Hyperbaric Oxygen Therapy on Microvascular Diabetic Complications and Metabolic Profile among Patients with Type 2 Diabetes Mellitus - Abdulhakeem Al-Rawahi (Oman Medical Journal, 2020)
Hyperbaric oxygen therapy (HBOT) has been suggested as a valuable addition to conventional treatment for a variety of indications, including delayed radiation injury, necrotizing soft tissue infections, and chronic wounds. By increasing the blood oxygen content, HBOT creates a favorable gradient for the diffusion of oxygen into the tissues. In hypoxic tissues, the enhanced oxygen supply has multiple effects that may benefit wound healing.